Analysis of the Environmental Impact of Using Sunblock on Gili Air Island, West Lombok - Muhamad Aryanang Isal (Journal of Law, Politic and Humanities, 2024)
Environmental destruction in the Gili Air area has reached an alarming phase, with many business actors throwing their kitchen waste into the sea, climate change and illegal fishing activities. The level of damage to coral reefs caused by human actions can be categorized as serious damage, because the public's perception of environmental awareness is still low. There is exploitation of coral reefs to fulfill the economy in the short term. One of the problems with environmental damage is the use of sunblock.  Although, sunblock Very beneficial for the skin, but in reality it actually brings disaster to marine life. Some countries have even banned its use sunblock made from these chemicals, considering that their impact is quite large in environmental damage. This research is about the smart regulation approach as a new perspective in observing environmental damage which is doctrinaire by using conceptual studies regarding the nature of the environment and the practice of using sunblock. The research results explain First, Hawaii created a law (UU) that prohibits distribution sunblock containing one of these chemicals. Coming into force on January 1 2019, this is the first law in the world to prohibit its use sunblock which contain chemicals that damage the environment in marine tourism areas.